Strengthening the Synergy between Bamuskal and the Village Government in Realizing Good Village Governance Based on Community Participation - ADJI SURADJI; R. Widodo Triputro; Rumsari Hadi Sumarto; Supardal Supardal; Saryana Saryana; Supami Supami (SWAGATI : Journal of Community Service, 2026)
This community service program aimed to strengthen the synergy between the Kalurahan Consultative Body (Bamuskal) and the Petir Village Government in realizing good village governance based on community participation. The synergy between these two institutions is an essential factor in creating village governance that is transparent, accountable, participatory, and responsive to community needs. Several problems identified at the village level include limited institutional harmonization, weak communication between institutions, and the suboptimal involvement of the community in village development planning and supervision processes. The implementation methods of this community service program included socialization activities, participatory discussion forums, institutional assistance, and capacity building for village government officials and Bamuskal members. The activities were carried out using a participatory approach through interactive lectures, case studies, and joint deliberation sessions to develop a common understanding regarding the functions, duties, and partnership patterns between Bamuskal and the Petir Village Government. The evaluation process was conducted through observation of participant involvement, reflective discussions, and identification of changes in participants’ understanding before and after the program. The results of the program showed an improvement in participants’ understanding of the importance of institutional synergy in village governance implementation. In addition, a shared commitment was established between Bamuskal and the Kalurahan Government to improve coordination, transparency, and community participation in village policymaking. Strengthening this synergy serves as an important foundation for supporting democratic, innovative, and sustainable village governance. Therefore, this community service activity contributes to enhancing village institutional capacity in realizing community participation-based good village governance.